Scurrula ferruginea (Jack) Danser from Western Peninsula of India - Bennet, S. S. R.; Sahni, K. C. (Indian Forester, 1977)
Seurrula ferruginea (Jack) Danser, hitherto reported from Burma, Yunnan, Malay Peninsula, Sumatra, Borneo, Palwan and W. Java, has been reported from Western Peninsula of India, an area far away from its known area of distribution. This is another instance of disjunct distribution of plants common to W. Ghats and areas adjacent to E. India.